EFEKTIVITAS TEKNIK FLUSHING TERHADAP PATENSI DAN KOMPLIKASI PERIPHERALLY INSERTED VENOUS CATHETER (PIVC): LITERATURE REVIEW - Natallia Delydia Kolopita; Helen Sri Rezeki; Grace Florencia (Jurnal Kesehatan, 2025)
Variations in the practice of flushing peripheral intravenous catheters (PIVCs), which are not yet standardised globally, have the potential to reduce catheter patency and increase the risk of complications such as obstruction, phlebitis, infiltration, and infection. This issue is of high urgency because it has a direct impact on patient safety, the effectiveness of intravenous therapy, and the efficiency of nursing services. Inconsistencies in flushing techniques, volumes, and frequencies indicate a gap between theory and practice, particularly in middle-income country healthcare facilities that lack evidence-based guidelines. This study aims to evaluate the effectiveness of various flushing techniques on PIVC patency and complications to strengthen the basis for evidence-based nursing practice and promote standardisation of clinical procedures. This study is a systematic literature review using the PICOT framework and following the PRISMA guidelines. Literature searches were conducted on PubMed, Scopus, ProQuest, and ScienceDirect for publications from 2015 to 2025. Inclusion criteria included primary quantitative studies examining 0.9% NaCl flushing techniques on PIVC patency and complication outcomes. Of the 38 initial records, five studies met the inclusion criteria and were analysed using a comparative-thematic synthesis approach to identify patterns of practice and the effectiveness of the intervention. The results showed that the pulsatile push–pause technique with a volume of 5–10 mL of 0.9% NaCl was consistently more effective than the continuous technique in maintaining patency and reducing complications. Variation in implementation remained high due to workload, training limitations, and the absence of standard protocols. This review emphasises the importance of evidence-based standardisation of flushing and large-scale, multicentre follow-up studies to strengthen global consensus and clinical application in various service contexts.